Jet radius dependence of dijet momentum balance and suppression in Pb + Pb collisions at 5.02 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; et al. (Physical review, 2024)
This paper describes a measurement of the jet radius dependence of the dijet momentum balance between leading back-to-back jets in 1.72nb−1 of Pb+Pb collisions collected in 2018 and 255pb−1 of 𝑝⁢𝑝 collisions collected in 2017 by the ATLAS detector at the LHC. Both datasets were collected at √𝑠NN=5.02 TeV. Jets are reconstructed using the anti-𝑘𝑡 algorithm with jet radius parameters 𝑅=0.2, 0.3, 0.4, 0.5, and 0.6. The dijet momentum balance distributions are constructed for leading jets with transverse momentum 𝑝T from 100 to 562 GeV for 𝑅=0.2, 0.3, and 0.4 jets, and from 158 to 562 GeV for 𝑅=0.5 and 0.6 jets. The absolutely normalized dijet momentum balance distributions are constructed to compare measurements of the dijet yields in Pb+Pb collisions directly to the dijet cross sections in 𝑝⁢𝑝 collisions. For all jet radii considered here, there is a suppression of more balanced dijets in Pb+Pb collisions compared with 𝑝⁢𝑝 collisions, while for more imbalanced dijets there is an enhancement. There is a jet radius dependence to the dijet yields, being stronger for more imbalanced dijets than for more balanced dijets. Additionally, jet pair nuclear modification factors are measured. The subleading jet yields are found to be more suppressed than leading jet yields in dijets. A jet radius dependence of the pair nuclear modification factors is observed, with the suppression decreasing with increasing jet radius. These measurements provide new constraints on jet quenching scenarios in the quark-gluon plasma.